Mothers, fathers, sons, and daughters: Are there sex differences in the organization of secure base behavior during early childhood - Fernandes, Carla (2018)
Recent empirical studies reporting sex differences in attachment relationships have prompted investigators to consider why and under what conditions such results might be observed. This study was designed to explore possibilities of identifying sex differences in the organization of attachment-relevant behavior during early childhood. Observations of 119 children (59 boys) with their mothers and (separately) with their fathers were completed and children were described using the AQS. Results indicated that girls and boys did not differ with respect to global attachment security but at more specific level analyses revealed differences between parents that reflected differences in the behaviors of girls vs. boys with mothers and fathers. Our findings contradict arguments from evolutionary psychologists claiming that sex differences in attachment organization arise during middle childhood. By adopting an attachment measure sensitive to the possibility of behavioral sex differences our data suggest that such differences may be detectable earlier in development. Moreover, these differences are subtle and nuanced and do not suggest large sex differences in attachment security per se.